Effect of Supplementing Wet Distillers’ Grains with Solubles to Maize Silage Based Diet on Performance of Growing Nellore Jodipi Ram Lambs - Naveena, K; Ravi, A.; Devasena, B.; Shakila, S. (Indian Journal of Animal Nutrition, 2020)
The objective of the study was to evaluate performance of ram lambs supplemented with distillers grains with solubles (DGS) under intensive system. In a completely randomized design, 24 growing Nellore Jodipi ram lambs were divided into 4 equal groups of six each.  Corn silage was fed  ad libitum to all the rams, basal diet was supplemented with DDGS  at 1.0% BW in control group (T1), whereas  WDGS was supplemented  at 1.0, 1.5 and 2.0 % BW in groupsT2, T3 and T4, respectively.The average daily gain (g) of 105.4, 69.1, 81.6, and 89.5 was recorded recorded in T1 to T4 fed lambs respectively, was higher (P